Szenci Molnár Albert munkássága az utolsó hatvan esztendő európai kutatási eredményeinek tükrében - Szabó, András (Studia Litteraria, 2026)
Until the middle of the 20th century, research in the history of culture, literature, and church history was mainly interested in the Reformation and Humanism of the 16th century, while after 1550, including the first two decades of the 17th century, it was a kind of “no man’s land”, which most people did not see worth dealing with. After a few early and pioneering studies of the 1960s, scholars witnessed the beginning of a more thorough study concerning this very period. It was due to the publication of basic handbooks, book series, and source editions, which led to an increase of the scholarly attention paid to this previously neglected period. There was also a major technological development, thanks to the personal computer and the Internet. After 1990, international scholarship opportunities opened up (now without domestic restrictions), and this had an inspiring effect on Molnár’s research, his life and his oeuvre as well. Between 1993 and 2003, a new critical edition of the Diary was completed, with commentaries and a Hungarian translation. It is possible to produce a similar edition of the correspondence, an edition of the Latin poems (pieces of which are turning up one after the other as a result of the digital publications), and perhaps someone will eventually start working on a monograph on him. This study goes through the research and publications that have made it possible to produce a virtual “map” of the work of this versatile Hungarian writer, who lived in Germany for thirty years, but enriched the Hungarian culture as well, as a theologian, a grammarian, a translator and a poet as well.